2020
DOI: 10.1093/ecco-jcc/jjaa143
|View full text |Cite
|
Sign up to set email alerts
|

Gut Microbiota-driven Drug Metabolism in Inflammatory Bowel Disease

Abstract: Abstract Background and aims The gut microbiota plays an important role in the metabolization and modulation of several types of drugs. With this study we aimed to review the literature about microbial drug metabolism of medication prescribed in inflammatory bowel disease practice. Methods Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(30 citation statements)
references
References 71 publications
0
29
0
1
Order By: Relevance
“…The effect of some of the above-mentioned drugs on gut microbiota are summarized in Table 2 . Interestingly some drugs that are used for treatment of IBD requires metabolic activation via the gut microbiota e.g., sulfasalazine, balsalazide (mesalamine prodrug), olsalazine, and methotrexates ( Crouwel et al, 2020 ).…”
Section: Effect Of Ibd Medications On Gut Microbiotamentioning
confidence: 99%
“…The effect of some of the above-mentioned drugs on gut microbiota are summarized in Table 2 . Interestingly some drugs that are used for treatment of IBD requires metabolic activation via the gut microbiota e.g., sulfasalazine, balsalazide (mesalamine prodrug), olsalazine, and methotrexates ( Crouwel et al, 2020 ).…”
Section: Effect Of Ibd Medications On Gut Microbiotamentioning
confidence: 99%
“…As an autoimmune disease closely related to intestinal microbes, the occurrence of inflammatory bowel disease (IBD) was often accompanied by gut microbiome dysbiosis. A study suggested that the human intestinal microbiome had an important influence on the drug metabolism and efficacy of IBD ( 25 ). Currently, there are limited studies on the association between the candidate intestinal bacteria found in this study and complex traits.…”
Section: Discussionmentioning
confidence: 99%
“…133 Over 180 orally administered drugs are now known to be metabolized by gut microbiota. 10,11,33,134,135 Microbiota drug metabolism can lead to significant inter-individual pharmacokinetic variability. 136 For example, a strain of Eggerthella lenta capable of inactivating the cardiac glycoside drug digoxin is estimated to inhabit the guts of 40% of the global population.…”
Section: Prediction Of Microbiome-drug Interactionsmentioning
confidence: 99%